Role of the medial septal area on pilocarpine-induced salivary secretion and water intake - Paulin, Renata Fabris; Menani, José Vanderlei [UNESP]; Colombari, Eduardo [UNESP]; Paula, Patricia Maria de [UNESP]; Almeida Colombari, Debora Simoes [UNESP] (Elsevier B.V., 2009)
Peripheral injection of pilocarpine, a cholinergic muscarinic agonist, induces salivation, water intake and hypertension. The medial septal area (MSA) is involved in cardiovascular control and fluid-electrolyte balance. Therefore, the effects of lesions or muscarinic cholinergic blockade in the MSA on the salivation, water intake and pressor responses induced by peripheral pilocarpine (4 mu mol/kg of body weight) were investigated. Male Holtzman rats with stainless steel cannulas implanted in the MSA or submitted to electrolytic lesion of MSA were used. MSA lesion (I day) reduced the salivation (262 45 vs. sham: 501 +/- 30 mg/7 min) and water intake (2.6 +/- 0.4 vs. sham: 4 +/- 0.4 ml/1 h) induced by intraperitoneal pilocarpine, whereas 15-day MSA lesion reduced only the pilocarpine-induced water intake (2.3 +/- 0.5 ml/1 h). Pre-treatment with the muscarinic cholinergic antagonist atropine methyl bromide (4 nmol/0.5 mu l) into MSA also reduced the pilocarpine-induced salivation (420 +/- 33 mg/7 min) and water intake (1.4 +/- 0.4 ml/1 h). Conversely, MSA lesions or the blockade of muscarinic receptors in the MSA did not change the pressor response induced by intravenous pilocarpine. The results show that MSA and its muscarinic receptors are part of the forebrain circuitry activated by peripheral pilocarpine that induce salivary secretion and water intake. Moreover, they suggest that different central mechanisms are involved in the salivatory, dipsogenic and cardiovascular effects of peripheral pilocarpine in rats. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Salivation; Thirst; Salivary gland; Atropine; Arterial pressure; Cholinergic receptor